Islamic banking and capital market performance in Indonesia, the lesson from pandemic Covid-19 - Rachman, M Aulia; Budiantoro, Risanda A (Indonesian Journal of Islamic Economics Research, 2024)
The Covid-19 pandemic caused panic on global financial markets and had an impact on a global recession. This research will examine the impact of Pandemic Covid-19 on the Performance of the Islamic Banking and Stock Market in Indonesia. The purpose of this study is to determine the different impacts of Islamic banking and the Islamic stock market in the long and short-term using the Autoregressive Distributed Lag (ARDL) method and using monthly data from January 2017 to December 2022. The results show that new cases of the Covid-19 pandemic actually have a positive impact on Islamic banking performance but not for stock market. Our findings have counter-estimations from several previous studies, therefore it may provide a new hypothesis of the performance of Islamic banking in Indonesia.